Transcriptional heterogeneity of stemness phenotypes in the ovarian epithelium - Lauren E. Carter (Nature Portfolio, 2021)
Using spheroids as a model, the authors report the molecular signatures of ovarian surface epithelial (OSE) cells exhibiting stemness phenotype under various conditions in vitro, and found that there is a large degree of heterogeneity in the transcriptional profiles of stem cells induced under different conditions. They suggest that maintenance of the OSE may not require a single stem cell population, but heterogeneous stem cells that can be induced transiently under diverse environmental cues.